Dampak Psikologis Perkawinan Anak Usia Dini: Studi Kasus di Keluarga Desa Mulyo Baru Surabaya - Achmad Nasrulloh Nasrul (JURNAL PENELITIAN KEISLAMAN, 2022)
There are many incidents when a child who is still very excited at a young age is forced to carry out a marriage due to various existing factors. For example, minimal knowledge, low economy, accidents (pregnant out of wedlock), to customs that have become family guidelines that must be applied to family members. his type of research is descriptive qualitative with data collection methods including observation, interviews, and documentation. In the findings of researchers in Simo Mulyo Baru village, Surabaya, there were 3 children who experienced this with various different factors. The results show that the psychological impact that appears on the marriage of a child varies, such as uncontrollable emotions, lack of understanding and understanding as a wife, lack of knowledge about household knowledge.